Effect of Endodontic Irrigants and Medicaments Mixed with Silver Nanoparticles against Biofilm Formation of Enterococcus faecalis - Ghahramani, Yasamin; Yaghoubi, Fariba; Motamedi, Ramin; Jamshidzade, Akram; Abbaszadegan, Abbas (Iranian Endodontic Journal, 2018)
Introduction: The aim of this study was to evaluate the effectiveness of chlorhexidine (CHX), sodium hypochlorite (NaOCl), calcium hydroxide (CH) and double antibiotic paste (DAP) mixed with silver nanoparticles (AgNPs) against Enterococcus faecalis. Methods and materials: Minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and biofilm formation inhibition (after 72 h) of the experimental substances alone or mixed with AgNPs were measured against E. faecalis using microtiter plate method. Bacterial cultures turbidity was measured using a spectrophotometer. All procedures were performed in triplicates. Results: The MIC values for CHX, NaOCl, CH and DAP were equal to 0.012, 1.25, 1.6 and 0.156 mg/mL, and their MBC’s were 0.025, 2.5, 0 and 0.625 mg/mL. After mixing them with AgNPs, the MIC’s for CHX, NaOCl, CH and DAP were reduced to 0.0032, 0.158, 0.2 and 0.0391 mg/mL, while their MBC’s were reduced to 0.0064, 0.0632, 0.401 and 0.0156 mg/mL. Biofilm formation inhibition occurred in higher dilutions of all irrigants and medicaments as they were mixed with Ag NPs. Conclusions: Adding AgNPs resulted in an increased antimicrobial activity at the tested dilutions for all experimental substances. More investigations in in vivo conditions are required to confirm the results of this study. Keywords: Calcium Hydroxide; Chlorhexidine; Double Antibiotic Paste; Enterococcus Faecalis; Silver Nanoparticles; Sodium Hypochlorite